Gender and Specialty Influence on Narcissism in University Students : Pengaruh Gender dan Keistimewaan terhadap Narsisme pada Mahasiswa - Fatima Kazem Owaid; Assistant Professor Hanaa Sadiq Al-Badran (Academia Open, 2024)
Background: Narcissistic personality traits have garnered increasing attention in psychological research, particularly within academic environments where student behavior and performance are critical. Understanding these traits and their influencing factors is essential for improving student well-being and academic outcomes. Specific Background: The impact of gender and field of study on narcissistic traits among university students remains underexplored. Kernberg's (1970) theoretical framework provides a basis for investigating these traits through empirical measures. Knowledge Gap: While previous studies have examined narcissism broadly, there is limited research focusing specifically on how gender and academic specialization affect narcissistic traits among university students. Aims: This study aimed to identify narcissistic personality traits among university students and examine variations based on gender and field of study using a newly developed Narcissistic Personality Scale. Results: The research, involving 376 students from the University of Basra, utilized a 35-item scale validated through rigorous psychometric testing. The results indicated that the average narcissism score was significantly higher than the hypothesized mean. Male students exhibited higher levels of narcissism compared to female students, and humanities students scored higher than their scientific counterparts. Novelty: This study provides new insights into the prevalence and variance of narcissistic traits among university students, highlighting significant differences related to gender and academic specialization. Implications: The findings underscore the need for university programs to address narcissistic traits and their impact on student behavior and academic performance. Future research should investigate the longitudinal effects of narcissism and evaluate interventions aimed at reducing these traits. Highlights: Gender differences: males show higher narcissism. Humanities students exhibit more narcissistic traits. Calls for targeted university interventions. Keywords: narcissistic personality, university students, gender differences, academic specialization, psychometric scale